PENERAPAN METODE PROCESS COSTING DALAM PENETAPAN HARGA POKOK PRODUKSI KENDANG JIMBE (Studi Pada Usaha Bubut Kayu UD. Cahaya Timur di Kota Blitar) - Fardati, Ikfina (Jurnal Ilmiah Mahasiswa FEB, 2017)
The aim of this study is to analyze the calculation of production cost at UD. Cahaya Timur. The product tht used for the study is kendang jimbe 30 cm size. Type of it is descriptive research with case study approach. Cost calculation method of production used is Process Costing Method. The production of kendang jimbe through 3 parts of production these are part of the lathe, part of the varnish and assembly parts. The calculation of cost of goods manufactured in each pasrt of production by taking into account the cost of raw materials, direst labor costs, and factory overhead costs. The result showed that calculation of production using process costing method is lower than calculation performed by companies using traditional methods. In addition by using process costing method is expected to be more efficient and accurate.Keywords: Costs of goods manufactured, Process costing method